On stochastic comparisons of energy functions with applications - Broderick O. Oluyede (International Journal of Mathematics and Mathematical Sciences)
We develop simple methods for the stochastic comparisons of informational energy functions. We introduce modified informational energy functions and uncertainty of parameter functions are introduced for models with realistic parameter spaces. We present inequalities, comparisons, and applications including test procedures for testing the equality of informational energy functions. Some illustrative examples are also presented.